Distribution Network Efficiency Improvement Based on Fuzzy Multi-objective Method - Ramadoni Syahputra; Imam Robandi; Mochamad Ashari (Institut Teknologi Sepuluh Nopember, 2014)
This paper presents a reconfiguration methodology based on a fuzzy multi-objective approach for achieving the minimum active power loss and the maximum voltage magnitude of radial distribution networks with distributed generations in order to improve the distribution system efficiency. Multi-objective function are considered for load balancing among the feeders, minimization of the real power loss, and deviation of bus voltage, while subject to a radial network structure in which all loads must be energized. These objective functions are modeled with fuzzy sets to evaluate the imprecise nature of each objective. Originality of the research is that the fuzzy-based multi-objective optimization in reconfiguration of distribution network including the distributed generation. The implementation of the fuzzy multi-objective for distribution reconfiguration on a 77 bus distribution network with distributed generation is described. The simulation results show that a 1.80% of electric power distribution network efficiency improvement is achieved by the method